2022
DOI: 10.1038/s41586-022-05441-2
|View full text |Cite
|
Sign up to set email alerts
|

THP9 enhances seed protein content and nitrogen-use efficiency in maize

Abstract: The maize (Zea mays ssp. mays) wild ancestor, teosinte, has three times the seed protein content of most modern inbreds and hybrids, but the mechanisms responsible for this trait are unknown. We created a contiguous haplotype DNA sequence of a teosinte, Zea mays ssp. Parviglumis, with Trio-Binning, and map-based cloned a major high-protein QTL, teosinte high protein 9 (Thp9) on chromosome 9. Thp9 encodes an asparagine synthetase 4 that is highly expressed in teosinte, but not in the B73 inbred, where a deletio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 72 publications
(79 reference statements)
0
31
0
Order By: Relevance
“…These findings suggest new varieties with high GPC can be developed by pyramiding these superior alleles. While previous studies have suggested a negative correlation between grain yield and GPC in cereal crops [ 33 , 38 ], some QTLs for GPC have been found to have no negative effect on grain yield [ 37 , 39 , 40 ], indicating the potential for improving GPC without compromising yield by incorporating these QTLs into new varieties. However, as the grain yield of the 174 oat accessions in this study was not investigated, the effects of the identified GPC QTLs on grain yield remain unknown.…”
Section: Discussionmentioning
confidence: 98%
“…These findings suggest new varieties with high GPC can be developed by pyramiding these superior alleles. While previous studies have suggested a negative correlation between grain yield and GPC in cereal crops [ 33 , 38 ], some QTLs for GPC have been found to have no negative effect on grain yield [ 37 , 39 , 40 ], indicating the potential for improving GPC without compromising yield by incorporating these QTLs into new varieties. However, as the grain yield of the 174 oat accessions in this study was not investigated, the effects of the identified GPC QTLs on grain yield remain unknown.…”
Section: Discussionmentioning
confidence: 98%
“…In an earlier study, researchers have found that a 191-bp insertion in the intron affected the expression levels of the polyphenol oxidase gene, resulting in a lower PPO activity in wheat [ 35 ]. Recent research has also reported that THP9 encoded an asparagine synthetase 4 enzyme which was highly expressed in teosinte, but not in the B73 inbred, in which a deletion in the tenth intron of THP9-B73 caused incorrect splicing of THP9-B73 transcripts [ 36 ]. In this paper, we also induced a 36-bp deletion (Del36) in the fifth intron of G-GmPAP14Z .…”
Section: Discussionmentioning
confidence: 99%
“…The starch content of the mature seeds was determined as has been previously described by [ 60 ]. For the protein quantification, 50 mg of powder was used for the protein extraction according to the method described by [ 61 ]. Then, the protein content was measured using a Bradford Protein Assay Kit (PC0010, Solarbio, Beijing, China).…”
Section: Methodsmentioning
confidence: 99%